2017
DOI: 10.1037/vio0000036
|View full text |Cite
|
Sign up to set email alerts
|

Empirical investigation of a model of sexual minority specific and general risk factors for intimate partner violence among lesbian women.

Abstract: Objective This study proposed and tested the first conceptual model of sexual minority specific (discrimination, internalized homophobia) and more general risk factors (perpetrator and partner alcohol use, anger, relationship satisfaction) for intimate partner violence among partnered lesbian women. Method Self-identified lesbian women (N=1048) were recruited from online market research panels. Participants completed an online survey that included measures of minority stress, anger, alcohol use and alcohol-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 66 publications
(114 reference statements)
6
46
1
3
Order By: Relevance
“…Women who were in a romantic relationship with another woman were recruited as part of a larger project that examined sexual minority stress, alcohol use, and intimate partner violence. Findings associated with intimate partner violence and discrepant alcohol use among lesbian women gleaned from this dataset have been reported elsewhere (Kelley, Lewis, & Mason, 2015; Lewis et al, 2015; Lewis, Mason, Winstead, & Kelley, 2016). …”
supporting
confidence: 66%
“…Women who were in a romantic relationship with another woman were recruited as part of a larger project that examined sexual minority stress, alcohol use, and intimate partner violence. Findings associated with intimate partner violence and discrepant alcohol use among lesbian women gleaned from this dataset have been reported elsewhere (Kelley, Lewis, & Mason, 2015; Lewis et al, 2015; Lewis, Mason, Winstead, & Kelley, 2016). …”
supporting
confidence: 66%
“…The DDQ is used widely among young adults 44,45 and SMW 46,47 and has shown strong psychometric properties. [48][49][50][51] Alcohol consequences. Participants who reported drinking in the past month completed the Brief Young Adult Alcohol Consequences Questionnaire (B-YAACQ).…”
Section: Methodsmentioning
confidence: 99%
“…Over the past decade, several studies have identified correlations between internalized homophobia/homonegativity and perpetration of physical IPV ( Balsam & Szymanski, 2005 ; Bartholomew, Regan, Oram, et al, 2008 ; Edwards & Sylaska, 2013 ; Lewis, Mason, Winstead, & Kelley, 2017 ), sexual IPV ( Balsam & Szymanski, 2005 ; Edwards & Sylaska, 2013 ; Finneran & Stephenson, 2014 ), and emotional/psychological IPV ( Bartholomew, Regan, Oram, et al, 2008 ). Homophobic discrimination and sexual orientation concealment have been identified as correlates of perpetration of physical IPV ( Edwards & Sylaska, 2013 ; Lewis et al, 2016 ). Edwards and Sylaska (2013) showed a positive relationship between sexual orientation victimization and emotional/psychological IPV.…”
Section: Introductionmentioning
confidence: 99%